1998
DOI: 10.1159/000020841
|View full text |Cite
|
Sign up to set email alerts
|

Effect of in utero Infusion Route on Lymphocyte Distribution in Fetal Rat Tissues

Abstract: Infusion of cells into the fetus is a new form of intrauterine therapy for several genetic disorders. The effect of in utero infusion routes on labelled lymphocyte distribution in fetal rat organs was investigated. Fetuses, 14–16 days of gestation, were infused in utero with a Hoechst 33342 (bis-benzamide) labelled lymphocyte and FITC-labelled polystyrene bead mixture via four routes: intraperitoneal, intraplacental, intra-amniotic, and intravenous. The distribution within tissues was evaluated in frozen secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…There have been several modes of antigen exposure utilized for delivering donor cells or genes during early gestation in animal models. These include intravascular[ 7 , 8 ], intracardiac[ 9 ], intraperitoneal[ 10 , 11 ], intraplacental[ 5 , 6 ], and intraamniotic injection. [ 12 ] Because of technical limitations, most of the studies were performed at later gestational stages than our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been several modes of antigen exposure utilized for delivering donor cells or genes during early gestation in animal models. These include intravascular[ 7 , 8 ], intracardiac[ 9 ], intraperitoneal[ 10 , 11 ], intraplacental[ 5 , 6 ], and intraamniotic injection. [ 12 ] Because of technical limitations, most of the studies were performed at later gestational stages than our study.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, there have been previous studies utilizing intraplacental bone marrow transplantation in the early gestational mouse model. The classical studies of Fleischman and Mintz [ 5 , 6 ] demonstrated hematopoietic engraftment and chimerism after intraplacental injection of hematopoietic cells, but tolerance was not investigated. However, in those studies, the placenta was blindly injected, and delivery of the cells to the fetal circulation was inconsistent.…”
Section: Introductionmentioning
confidence: 99%